The influencing factors of sustainable development of e-commerce in small and medium-sized enterprises in China - Xuesongzi, Feng; Abdul Halim, Hasliza; Ke, Dong (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The influence of COVID-19 not only affected the economy but also changes marketing channels. E-commerce has become a new platform for small and medium-sized enterprises (SMEs) to develop their businesses; however, there are still some new problems faced by SMEs in E-commerce because of limited scales. This study try to used SWOT analysis to show the status quo of SMEs in e-commerce and establish the AHP evaluation index system. The system first used questionnaires to score the internal and external factors that affected the sustainable development of E-commerce for SMEs and constructed a judgment matrix to be compared. The result showed that SMEs should adopt the WO striving strategy and expand market share to promote the transformation of their own disadvantages and society’s environment. The study tried to help SMEs find sustainable development in E-commerce after being influenced by COVID-19. In addition, past research have focused on large and medium-sized enterprises and this study trying to focused on SMEs which as a new research field for E-commerce in China.